ANALISIS DETERMINAN STRUKTUR KEUANGAN PADA PERUSAHAAN MANUFAKTUR YANG GO PUBLIC DI BURSA EFEK INDONESIA: STUDI EMPIRIS BERDASARKAN HUTANG JANGKA PANJANG DAN HUTANG JANGKA PENDEK - GOLCONDA, HILL HILARY (JURNAL ILMIAH MAHASISWA MANAJEMEN, 2012)
This study aims to determine the determinants of financial structure affects the ratio of long-term debt (LDTR), the ratio of short-term debt (SDTR) and the ratio of total debt (TDR) to total assets in the manufacturing sector to go public in Indonesia. This study uses secondary data by the number of samples used by 60 manufacturing companies listed on the Indonesia Stock Exchange during the four-year period 2007-2010 and have met certain criteria. The results showed that the TANG (asset tangibility) has a positive and significant relationship with long-term debt and total debt. Variable PROF (profitability) has a negative relationship with long-term debt and total debt. CASH (cash) has a negative relationship with short-term debt and total debt. OCL (other current liabilities) has a positive relationship with short-term debt and significant. CAPINT (capital intensity) has a positive relationship with total debt. SIZE (the size of the company) has a positive relationship with total debt. ACPAY (accounts payable) has a positive and significant relationship with total debt. ACREC (accounts receivable) has a negative and significant relationship with total debt.